Genome-Wide Identification of Sultr Genes in Malus domestica and Low Sulfur-Induced MhSultr3;1a to Increase Cysteine-Improving Growth - Xun, Mi; Song, Jianfei; Shi, Junyuan; Li, Jiaqi; Shi, Yujia; Yan, Junhong; Zhang, Weiwei; Yang, Hongqiang (Frontiers in Plant Science, 2021)
Sulfur (S) is an essential nutrient for plant growth and development. Sulfate transporter (Sultr) is critical for sulfate (SO42-) uptake from soil by roots in higher plants. However, the knowledge about Sultrs in apple (Malus domestica) is scarce. Here, 9 putative MdSultrs were identified and classified into 2 groups according to the analysis of the phylogenetic relationship, gene structures, and conserved motifs. Furthermore, various cis-regulatory elements related to abiotic stress and plant hormone responsiveness were found in the promoter regions of the MdSultrs. These MdSultrs exhibited tissue-specific expression patterns and responded to low S, ABA, IAA and MeJA. Among them, MdSultr3;1a was especially expressed in roots and induced by low S. The uptake of SO42- in cultivated apple depends on roots of its rootstock, MhSultr3;1a was isolated from Malus hupehensis roots used as rootstock. MhSultr3;1a shared 99.85% homology with MdSultr3;1a and localized on the plasma membrane and nucleus membrane. Further function characterization revealed that MhSultr3;1a complemented a sulfate transport-deficient yeast mutant, improved growth of yeast and apple calli under low S condition. MhSultr3;1a-overexpressing apple calli showed higher fresh weight than that of wild type (WT) under low S treatment because of increased SO42- and cysteine (Cys) content. These results demonstrate that MhSultr3;1a may increased the content of SO42- and Cys to meet the demand for S-containing compounds and improved better growth under S-limiting conditions.